URGENSI MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM - Awalia, Rubi; Saputra, Husyin; Supatmi, Supatmi (ILJ: Islamic Learning Journal, 2023)
Education management is the heart of education. To get a quality educational process, namely by having an educational component that is followed in the educational process itself. Therefore the urgency of a management is interesting to study, especially in improving the quality of education. This research is a literature study, using documentary data collection methods and content analysis. Educational institutions can be said to be of high quality if their educational inputs, processes and outputs can meet the requirements demanded by users of educational services, both internal and external. The concepts contained in education management require new innovations in order to be able to create useful quality education. To create quality Islamic education, a strategy must be implemented that is oriented to the needs and expectations of customers/ customers. stakeholder.